Examining the Traditional Methods of Crime Control in an Identified Traditional Community: An Invitation to the Socio-Anthropological Jurisprudence of Mpam Community of Ahiazu Mbaise, Imo State - Hyginus Obinna Ogbonna; Chidi Slessor Mbah; C.A.C Chukwunka; Benedict Ibukun Ajayi (Mediterranean Journal of Social Sciences, 2023)
The paper focuses on assessing the traditional methods of crime control in an identified traditional community. Its main objective is to examine critically the traditional methods of crime control in a particular traditional community so as to appreciate the effectiveness of the traditional methods in crime control. To achieve this objective, the traditional community of Mpam in Ahiazu Mbaise L.G.A of Imo state was identified. An ethnographic non-participant descriptive method of analysis was used. Its sources of information included observations as well as secondary sources (books, journals, and the internet). A few theories were identified and reviewed, and the Control theory of Crime was adopted as the theoretical framework. In its investigation, some findings were made; these include: Crime Control measures serve as deterrents to prevent people from criminal behaviors; crime control methods in traditional societies may be primitive in nature, but they help in effectively controlling crimes among the natives; besides, society itself may be contributory in causing people to engage in criminal behavior. The paper therefore concludes that, in as much as crime is inevitable in all human societies (modern or traditional) effective crime control methods are the remedy to combat crime to achieve societal harmony. And thus, recommends: government should encourage traditional societies to retain some of their traditional crime control methods that have proved to be effective in controlling crime among the people; the leadership of traditional societies should review and adjust some of their traditional crime control methods that may infringe on the individual’s human rights, inter alia. Received: 26 February 2023 / Accepted: 20 April 2023 / Published: 5 May 2023